School Well-being in Terms of Self-Determination and Patience in Vocational High School Students - Abdillah, Hafizh Zain; Rahman, Fauzi; Husna, Muniratul; Sitinjak, Charli; Hidayah, Nurul; Mujidin, Mujidin (Universitas Muhammadiyah Yogyakarta, 2022)
Previous research on school wellbeing has highlighted the need for its implementation in schools. This research aims to uncover two elements influencing school well-being: self-determination and patience. This study used quantitative methods with multiple linear regression analysis. The population in this study was 672 students of classes X, XI, and XII at SMK Muhammadiyah 1 Yogyakarta. The sampling technique employed in this study was cluster-random sampling with a sample of 178 students. The results showed an F-value of 27.182 with an absolute significance level (p-value) of 0.01, so the major hypothesis was accepted. The self-determination and patience variables simultaneously (together) could affect school well-being. The effect of self-determination on school well-being was 20%, while patience only contributed 3.67%. This research revealed (1) there was a positive influence of self-determination and patience on the well-being of vocational school students, (2) there was a positive effect of partial self-determination on school well-being, meaning that partial self-determination could predict school well-being, and (3) there was no partial positive effect of patience on school well-being, indicating that partial patience could not predict school well-being.